Transformer Less Voltage Quadrupler Based DC-DC Converter with Coupled Inductor and PI Filter for Increased Voltage Gain and Efficiency - C. Sujitha; S. Ravi; Bakary Diarra; Joseph Chuma (Institute of Advanced Engineering and Science, 2016)
In this paper a voltage quadrupler dc-dc converter with coupled inductor and π filter is presented. The use of the coupled inductor reduces the high leakage inductance which is present in a transformer enabled converter. The output ripples in the converter is reduced by providing a π filter. The interleaved voltage quadrupler is used in this system in order to boost the output voltage. The voltage multiplier improves the output voltage gain. The main advantage of this system is more voltage gain when compared with the transformer eneabled circuit and the overall efficiency of the system is improved. The circuit is simple to control. As a final point of this research, the simulation and the hardware investigational results are presented to demonstrate the effectiveness of this proposed converter.